Psychology and work today : an introduction to industrial and organizational psychology - Schultz, Duane P., ....-; Schultz, Sydney Ellen, ....- (Upper Saddle River, N.J. : Pearson Education, 2009)
For undergraduate-level courses in Industrial and Organizational Psychology, Business Psychology, Personnel Psychology and Applied Psychology. Psychology and Work Today provides an invaluable foundation for anyone entering today's global business and industrial world. This informative, sophisticated, and entertaining text teaches students about the nature of work in modern society. By focusing on the practical and applied rather than the scientific ideal, the authors demonstrate how industrial-organizational psychology directly impacts our lives as job applicants, trainees, employees, managers, and consumers.
Includes bibliographical references and index.
Keywords: Psychology, Industrial; Organizational behavior; Psychologie